The Influence of Organizational Culture and Work Motivation on Employee Performance at The Alfamidi Office in Ambon City - Asiani Sijabat (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze the influence of organizational culture and work motivation on employee performance at the Alfamidi office in Ambon City. The study used a quantitative approach with a survey method of 42 respondents, who were Alfamidi employees in Ambon City. Data collection was carried out by distributing questionnaires using a five-point Likert scale. Data analysis used multiple linear regression with the help of SPSS. The results of the study indicate that organizational culture and work motivation have a positive and significant influence on employee performance. Partial test results indicate that organizational culture significantly influences employee performance. Simultaneous test results indicate that organizational culture and work motivation simultaneously have a significant influence on employee performance. These findings indicate that companies need to strengthen organizational culture and increase work motivation to sustainably improve employee productivity and work quality.